Applications of near-infrared spectroscopy in "anaerobic" diagnostics - SmO2 kinetics reflect PCr dephosphorylation and correlate with maximal lactate accumulation and maximal pedalling rate - Dunst, A. K.; Manunzio, C.; Feldmann, A.; Hesse, C. (Biology of Sport, 2023)
We investigated the relationship of the time-dependent behaviour of muscle oxygen saturation SmO2(t), phosphagen energy supply WPCr(t) and blood lactate accumulation Delta-BLC(t) during a 60-s all-out cycling sprint and tested SmO2(t) for correlations with the end of the fatigue-free state tFf, maximal pedalling rate PRmax and maximal blood lactate accumulation rate vLamax. Nine male elite track cyclists performed four maximal sprints (3, 8, 12, 60 s) on a cycle ergometer. Crank force and cadence were monitored continuously to determine PRmax and tFf based on force-velocity profiles. SmO2 of the vastus lateralis muscle and respiratory gases were measured until the 30th minute after exercise. WPCr was calculated based on the fast component of the post-exercise oxygen uptake for each sprint. Before and for 30 minutes after each sprint, capillary blood samples were taken to determine the associated Delta-BLC. Temporal changes of SmO2, WPCr and ?BLC were analysed via non-linear regression analysis. vLamax was calculated based on Delta-BLC(t) as the highest blood lactate accumulation rate. All models showed excellent quality (R2 > 0.95). The time constant of SmO2(t) tSmO2 = 2.93±0.65 s was correlated with the time constant of WPCr(t) tPCr = 3.23±0.67 s (r = 0.790, p < 0.012), vLamax = 0.95±0.18 mmol·l -1 ·s -1 (r = 0.768, p < 0.017) and PRmax = 299.51±14.70 rpm (r = -0.670, p < 0.049). tFf was correlated with tSmO2 (r = 0.885, p < 0.001). Our results show a time-dependent reflection of SmO2 kinetics and phosphagen energy contribution during a 60-s maximal cycling sprint. A high vLamax results in a reduction, a high PRmax in an increase of the desaturation rate. The half-life of SmO2 desaturation indicates the end of the fatigue-free state.